The magnitude of the largest possible earthquake in the Muong La - Bac Yen fault zone - Duẩn, Bùi Văn; Thăng, Nguyễn Công; Vượng, Nguyễn Văn; Nguyên, Phạm Đình (Vietnam Journal of Earth Sciences, 2013)
This paper presents estimation result of the magnitude of the largest possible earthquake in the Muong La - Bac Yen fault zone, a seismic-source zone located in the Northwest of Vietnam. After investigating and analysing terrain, geomorphology, geological features, satellite and Shuttle Radar Topography Mission images and related earthquake data, several geometric-geodynamic characteristics of the Muong La - Bac Yen fault zone in the Present had been elucidated. The estimation of the magnitude of the largest possible earthquake in the Muong La - Bac Yen fault zone was based on these results. The study finally shows that 1) the Muong La - Bac Yen fault zone has expressed to be an active one in Present and may generate earthquakes in future; 2) the magnitude of the largest possible earthquake in the Muong La - Bac Yen fault zone is Mmax = 5.9 ± 0.3, corresponding to an average return period of 450 years